2013
DOI: 10.4085/1062-6050-48.2.06
|View full text |Cite
|
Sign up to set email alerts
|

Fulfillment of Work-Life Balance From the Organizational Perspective: A Case Study

Abstract: The foundation for a successful work environment in the NCAA Division I clinical setting potentially can center on the management style of the supervisor, especially one who promotes teamwork among his or her staff members. Although a family-friendly work environment is necessary for work-life balance, each member of the athletic training staff must have personal strategies in place to fully achieve a balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
76
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(84 citation statements)
references
References 0 publications
7
76
1
Order By: Relevance
“…For many of our female ATs, the time demands that are associated with full-time athletic training positions at the NCAA Division I setting appeared to be too much to allow an adequate balance of motherhood and a career. Interestingly, similarly to the findings of Mazerolle and Goodman 26 in a case study spotlighting several female ATs who were married with children, several of our female ATs were firm in their goal to remain in the NCAA Division I setting while managing both roles. Their persistence may benefit future female ATs, as mentorship has been revealed as necessary to retain more female ATs in this setting.…”
Section: Discussionsupporting
confidence: 48%
“…For many of our female ATs, the time demands that are associated with full-time athletic training positions at the NCAA Division I setting appeared to be too much to allow an adequate balance of motherhood and a career. Interestingly, similarly to the findings of Mazerolle and Goodman 26 in a case study spotlighting several female ATs who were married with children, several of our female ATs were firm in their goal to remain in the NCAA Division I setting while managing both roles. Their persistence may benefit future female ATs, as mentorship has been revealed as necessary to retain more female ATs in this setting.…”
Section: Discussionsupporting
confidence: 48%
“…4,5 Professional autonomy, particularly regarding work scheduling, is necessary to find WLB in the collegiate setting because it allows the AT the means to complete nonwork obligations around the time constraints placed on patient care, practice or game coverage, and administrative duties. Whereas our findings indicated a lack of professional autonomy, Mazerolle and Goodman 13 reported that it is possible to have in the collegiate setting and requires increased communication between supervisors and coworkers, as well as a team approach to patient care and job-sharing duties. Autonomy and social support not only can facilitate fulfillment of WLB but also are important factors in reducing organizational and professional turnover.…”
Section: Organizational Challengescontrasting
confidence: 50%
“…Furthermore, the head AT is a critical component in creating WLB for the AT and in mentoring, which can be associated with a supervisory role and has been suggested as an important socializing agent in the role of an AT and a means to facilitate WLB. 13 Work-life imbalance is inevitable for every working professional and can be influenced by a host of factors. Specifically, for those working in the sport culture, this can be a combination of organizational, personal, and socioeconomic factors.…”
mentioning
confidence: 99%
See 2 more Smart Citations